1998
DOI: 10.1111/j.1745-9125.1998.tb01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Drug and Disorder Problems: The Role of Place Managers*

Abstract: This article explores the role of place managers in controlling drug and disorder problems on 100 street blocks in Oakland, California. We use self‐reports from a sample of place managers to explore their role in changing the social and physical conditions of street‐block activity within the context of a randomized field trial in Oakland. On‐site observations of the changes in the social and physical conditions of 100 street blocks were conducted and used as our outcome measures. Our results suggest that stree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
2
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 24 publications
2
57
2
2
Order By: Relevance
“…We found that the fifty experimental street blocks targeted by the Beat Health program were also places that evidenced decreases in signs of disorder, decreases in males selling drugs, and increases in signs of civil behavior in public places when the social observation data were analyzed (Mazerolle, Roehl and Kadleck, 1998). Our finding that drug problems were more effectively controlled in the experimental sites (by the Beat Health Unit) than in the control sites (Patrol Division) were also supported in the calls for service data.…”
Section: Most Iirterventions Lead To Positive Changessupporting
confidence: 58%
See 3 more Smart Citations
“…We found that the fifty experimental street blocks targeted by the Beat Health program were also places that evidenced decreases in signs of disorder, decreases in males selling drugs, and increases in signs of civil behavior in public places when the social observation data were analyzed (Mazerolle, Roehl and Kadleck, 1998). Our finding that drug problems were more effectively controlled in the experimental sites (by the Beat Health Unit) than in the control sites (Patrol Division) were also supported in the calls for service data.…”
Section: Most Iirterventions Lead To Positive Changessupporting
confidence: 58%
“…We found that the level of place manager collective involvement in community activism was associated with decreases in signs of disorder and with increases in levels of signs of civil behavior in public places on the street blocks in our study. Levels of perceived street block cohesiveness were found to play a significant role in decreases in males selling drugs (Mazerolle, Kadleck and ' Roehl, 1998; see also Sampson, Raudenbush and Earls, 1997;Taylor, 1996). Individual, direct actions (e.g., calling 91 1) taken by place managers in an attempt to solve problems at specific target locations, however, were not associated with decreased levels of social and physical disorder on the street blocks in our study.…”
contrasting
confidence: 49%
See 2 more Smart Citations
“…An exception to the lack of independent observations of disorder at the level of ecological units rather than persons is found in research by Taylor and colleagues (Taylor, Shumaker, and Gottfredson 1985;Taylor, Gottfredson, and Brower 1984;Covington and Taylor 1991;Perkins et al 1992;Perkins and Taylor 1996; see also Mazerolle, Kadleck, and Roehl 1998). 5 Using observations conducted by teams of trained raters walking the streets, Taylor et al (1985) assessed 20% of all occupied face blocks in 66 Baltimore neighborhoods.…”
Section: Systematic Social Observation Of Disordermentioning
confidence: 99%